2005
DOI: 10.1111/j.1572-0241.2005.40360.x
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-Hexamethylpropylene Amineoxime Leukocyte Scintigraphy in Acute Pancreatitis: An Alternative to Contrast-Enhanced Computed Tomography?

Abstract: Our results show that leukocytes are related to the severity of local pancreatic damage in AP. Thus, LLS is a potential alternative technique to CECT for staging AP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…Previous studies in which scintigraphy with radionuclidelabeled leukocytes was used to detect infected pancreatic necrosis were limited to g-camera scintigraphy with leukocytes labeled with 111 In (5,6) or 99m Tc (7)(8)(9)(10). The use of 67 Ga SPECT/CT imaging, with high sensitivity and specificity, was also reported in this clinical context (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in which scintigraphy with radionuclidelabeled leukocytes was used to detect infected pancreatic necrosis were limited to g-camera scintigraphy with leukocytes labeled with 111 In (5,6) or 99m Tc (7)(8)(9)(10). The use of 67 Ga SPECT/CT imaging, with high sensitivity and specificity, was also reported in this clinical context (23).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have shown the usefulness of radionuclide-labeled leukocyte scintigraphy for the detection of infected pancreatic necrosis in patients with AP (5-10) and have even suggested it as an alternative to CECT for staging AP (10). However, these studies were limited to g-camera scintigraphy with leukocytes labeled with 111 In (5) or 99m Tc (7)(8)(9)(10), and image quality and resolution were unsatisfactory.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study we concluded that LLS could be an alternative technique to CECT for staging AP [23] . We have now extended that work by using a larger prospective series of patients with AP to evaluate specifically the utility of LLS with 99m Tc-HMPAO in the diagnosis of PN.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have shown the usefulness of scintigraphy using radionuclide-labeled leukocytes, a safe and non-invasive technique, as an indicator of pancreatic damage in patients with AP [17][18][19][20][21][22] . In previous research, we concluded that labeled leukocyte scintigraphy (LLS) may be an alternative to CECT for staging AP [23] .…”
mentioning
confidence: 99%